Transformation of strategic alliances in emerging markets. Volume II - Hyder, Akmal S.; Abraha, Desalegn (Emerald Publishing Limited, 2021)
There is much research into strategic business alliances in emerging markets, but none focuses on this form of collaboration within Europe's emerging economies. This is a critical absence, as the European transition region is not only different from other European and Western regions but also from other regions with developing economies. Partners in the European transition region have unique cultural and social backgrounds, and consequently, unique ways of doing business. Transformations of Strategic Alliances in Emerging Markets focuses on this important gap. This book, the second of a two-volume set, makes a unique contribution to emerging market research by investigating the transformation of alliances in Eastern and central Europe over the past forty years. It provides a conceptual framework to describe and analyse the formation, development and functional mechanisms of strategic alliances in the European transition region, ultimately offering an in-depth overview of the challenges and opportunities around strategic alliance formation in emerging European markets. Transformations of Strategic Alliances in Emerging Markets, Volume II , is a must-read for academics and postgraduate students of development economics and business administration.
Includes index.
Keywords: Strategic alliances (Business) -- Europe.; Investments, Foreign -- Europe.; Joint ventures -- Europe.; Business & Economics, Investments & Securities, Analysis & Trading Strategies.; Trade agreements.; elektronické knihy; electronic books